The Effectiveness of Art Therapy for Depression and Relevant Factors - Wu, Yuheng (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Art therapy (AT) is a method of treating psychological illnesses and improving mental health that uses artistic means. Depression is a medical condition that could cause changes in one’s feelings, thoughts, and behaviors. This paper focuses on testing the effectiveness of art therapy on depressive symptoms with its relevant factors by analyzing the most recent research progress in this field. With the evaluation of the paper, it can be concluded that depression symptoms can be reduced by art therapy. However, there are some limitations in the research reviewed in this article. Most research used subjective measures, which might not reflect the objective outcomes of participants. Additionally, most studies did not follow participants for a long period after the therapy. Future research could be done with more objective methods and procedures to test the long-term effect of art therapy on depression. This review can provide some suggestions to the development of effective treatments for individuals with depression.